Pulmonary complications of the inflammatory rheumatic diseases - Wisłowska, Małgorzata; Dereń, Dorota (Reumatologia/Rheumatology, 2005)
The respiratory system is involved in inflammatory rheumatic diseases. The pulmonary complications are a heterogeneous group of diseases. They can affect all sites of the respiratory system. This article presents different types of pulmonary complications, their symptoms and diagnosis. There have been found 18 cases (11%) with pulmonary complications on patients with inflammatory rheumatic diseases. There were pulmonary fibrosis, pleuritis and pleuritis in the past.